Closure of Nasal Septal Perforations Using a Diced Cartilage in Fascia Graft - Spatz, Cornelia; Kühnel, Thomas; Stegmann, Achim; Schwan, Franziska; Bumm, Klaus; Bohr, Christopher (Facial Plastic Surgery, 2024)
The spectrum of surgical techniques in the repair of nasal septal defects is wide. The objective of this study was to assess the feasibility of using a diced cartilage in fascia (DC-F) graft for successful closure of nasal septal perforations and to evaluate symptom reduction. This was a retrospective study of 18 patients undergoing surgical repair of symptomatic nasoseptal perforations of different etiologies using a DC-F graft from 2020 until 2021. The procedure was feasible in all of the 18 patients. Reconstruction of septal defects with a DC-F graft led to reduction of crust formation, reduction of epistaxis, and improvement of nasal breathing in 13 out of the 18 patients when seen for their 2-month follow-up. Reperforation occurred in three cases, leaving defects of 1, 7, and 5 mm in diameter. In one case, the reperforation was symptomatic. A DC-F graft proved to be a reliable and reproducible method for the closure of nasoseptal perforations of variable sizes, of different locations, and of different etiologies.
CRIS-Team Scopus Importer:2025-02-04